Thermogenic adipocytes: from cells to physiology and medicine - Berriel Diaz, Mauricio; Herzig, Stephan; Vegiopoulos, Alexandros (Metabolism, 2014)
The identification of active brown fat in humans has evoked widespread interest in the biology of non-shivering thermogenesis among basic and clinical researchers. As a consequence we have experienced a plethora of contributions related to cellular and molecular processes in thermogenic adipocytes as well as their function in the organismal context and their relevance to human physiology. In this review we focus on the cellular basis of non-shivering thermogenesis, particularly in relation to human health and metabolic disease. We provide an overview of the cellular function and distribution of thermogenic adipocytes in mouse and humans, and how this can be affected by environmental factors, such as prolonged cold exposure. We elaborate on recent evidence and open questions on the distinction of classical brown versus beige/brite adipocytes. Further, the origin of thermogenic adipocytes as well as current models for the recruitment of beige/brite adipocytes is discussed with an emphasis on the role of progenitor cells. Focusing on humans, we describe the expanding evidence for the activity, function and physiological relevance of thermogenic adipocytes. Finally, as the potential of thermogenic adipocyte activation as a therapeutic approach for the treatment of obesity and associated metabolic diseases becomes evident, we highlight goals and challenges for current research on the road to clinical translation.
Gesehen am 22.07.2020